Antimicrobial resistance in Neisseria gonorrhoeae in nine sentinel countries within the World Health Organization Enhanced Gonococcal Antimicrobial Surveillance Programme (EGASP), 2023: a retrospective observational studyResearch in context - Ismael Maatouk; Phiona Vumbugwa; Thitima Cherdtrakulkiat; Lon Say Heng; Irving Hoffman; Noel Palaypayon; Francis Kakooza; Rossaphorn Kittiyaowamarn; Peter Kyambadde; Monica M. Lahra; Pham Thi Lan; Venessa Maseko; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: The global spread of antimicrobial resistance (AMR) in Neisseria gonorrhoeae threatens empiric single-dose gonorrhoea treatment. Enhanced global AMR surveillance is imperative. We report i) gonococcal antimicrobial susceptibility and resistance data from 2023 in the World Health Organization Enhanced Gonococcal Antimicrobial Surveillance Programme (WHO EGASP) in the WHO Western Pacific Region (Cambodia, the Philippines, Viet Nam), Southeast Asian Region (Indonesia, Thailand), and African Region (Malawi, South Africa, Uganda, Zimbabwe), and ii) metadata of the gonorrhoea patients. Methods: In 2023, WHO EGASP included men with urethral discharge (n = 3498) and gonococcal isolates (n = 2491). Minimum inhibitory concentrations (MICs, mg/L) values were determined for ceftriaxone, cefixime, azithromycin, gentamicin, and ciprofloxacin using Etest (bioMérieux). Breakpoints from the European Committee on Antimicrobial Susceptibility Testing (EUCAST) were applied. Clinical and epidemiological variables associated with AMR isolates were assessed using univariable and multivariable logistic regression analyses of odds ratios. Findings: Overall, 3.8% (95% confidence interval (95% CI) 3.1–4.6%; 95/2487), 8.9% (95% CI 7.9–10.1%; 222/2484), 3.6% (95% CI 2.9–4.4%; 89/2487), and 95.3% (95% CI 93.2–97.5%; 1801/1890) of isolates were resistant to ceftriaxone, cefixime, azithromycin, and ciprofloxacin, respectively. All the ceftriaxone-resistant isolates were from Cambodia (15.3% (95% CI 11.5–20.1%), 42/274) and Viet Nam (20.4% (95% CI 15.9–25.7%), 53/260). In univariable analysis, ceftriaxone resistance was associated with travelling within the country during previous 30 days (OR 4.66, 95% CI 3.06–7.16; p < 0.001), and this association remained in multivariable analysis (aOR 4.12, 95% CI 2.65–6.65; p < 0.001). Interpretation: Resistance to ceftriaxone, cefixime, and azithromycin is a major global concern, and expanded and improved resistance surveillance is essential. The WHO EGASP has been substantially expanded in the recent years. Additionally, resistance breakpoints have been harmonised and test-of-cure, whole-genome sequencing, and extragenital sampling implemented, where feasible. Novel antimicrobials for gonorrhoea treatment are critical; zoliflodacin and gepotidacin are promising. Funding: WHO, Global Fund.